Caudatin Inhibits the Proliferation, Invasion, and Glycolysis of Osteosarcoma Cells via the Wnt/β- Catenin Pathway. (23rd December 2022) - Zhang, Yan; Sheng, Zhizhong; Su, Chi; Xia, Yuli; Chen, Xiangfan; Huang, Xiaobo; Li, Honglin; Ma, Changsheng; Wang, Ligang
Abstract : Background . Caudatin is a steroidal glycoside with reported anticancer activity in a variety of studies. Nevertheless, the role and mechanisms of caudatin in osteosarcoma (OS) remain unclear. In this study, we explored the potential anticancer effects of caudatin in OS cells and investigated the underlying mechanisms. Methods . Both the CCK8 proliferation assay and flow cytometry were employed to evaluate cell proliferation and apoptosis. A transwell assay was applied to determine cell invasion ability. Besides, glycolytic capacity was examined by measuring glucose consumption, lactic acid production, as well as ATP production. A western blot was utilized to assess the protein levels of β -catenin, CyclinD 1, C-myc, HK2 (Hexokinase 2), LDHA (lactate dehydrogenase), as well as epithelial-mesenchymal transition (EMT)-related markers. The inhibitory effect of caudatin on tumor growth was investigated using a xenograft tumorigenesis model. Results . Caudatin restrained cellular glycolysis, suppressed cell proliferation and invasion by reducing HK2 and LDHA expression and regulating the Wnt/ β -Catenin signaling pathway. Caudatin treatment caused the upregulation of E-cadherin and suppressed N-cadherin expression. Further, caudatin treatment impaired cell viability, invasion ability, and intracellular glycolysis level but induced apoptosis. The administration of BML 284 reversed the inhibitory effects of caudatin. Moreover, caudatin suppressed the tumorigenesis of OS cells in the xenograft model of nude mice. Conclusions . Our study revealed the anticancer effects of caudatin, including proliferation inhibition, cell invasion suppression, and glycolysis impairment. These effects seem to be executed through targeting the Wnt/ β -Catenin signaling pathway. These data indicate that caudatin may be formulated as a potential therapeutic for osteosarcoma.